Resilience capacity and vulnerability: The case of Slovakia - Aura Reggiani; Oto Hudec; Monika Siserova (European Regional Science Association (ERSA), 2016)
The concept of resilience has been recently investigated from the perspective of several disciplines. This extensive research has brought many approaches anchoring the key definitions, linked to both the notion of stability in dynamics (return to the previous equilibrium after a shock) and to the idea of adaptivity (absorption of the shock leading to new equilibria). Among the various definitions and measurements which can be found in the literature, the Resilience Capacity Index (RCI) classifies the most resilient regions and municipalities, in the case of external shocks, according to three different dimensions: a) economic; b) socio-demographic; and c) community-connectivity. However, the RCI should also be tested empirically versus other resilience/vulnerability indicators. This is the approach which will be used in the present paper. Vulnerability refers to the degree to which a system is susceptible to harm. In general, the concept of vulnerability has had limited attention in spatial economics. In the present paper, this concept will be adopted by analysing the dynamics of the unemployment growth rate, and comparing it to the RCI. In this context, the role of economic space is relevant, since the spatial units can provide good insights into resilience and vulnerability measures. The country of interest in this paper is Slovakia. Slovakia is a country in central eastern Europe which is bordered by the Czech Republic, Austria, Poland, Ukraine, and Hungary and presents interesting socio-economic-policy characteristics. The chosen spatial unit is at the district level. In the context of the 2007-2008 economic crisis, the RCI in the 79 Slovak districts is examined vs. vulnerability (based on the unemployment rate) in the first period of rising unemployment (2007-2011), as well as in the second period of following vulnerability/absorption to the economic shock (2011-2014). Similarly to previous research, the result show higher RCI in the major economic centres of Slovakia. In addition, a form of the west-east divide in RCI can also be seen. However, the reaction of the districts is ambiguous in terms of their vulnerability to the economic crisis. The more urban, export-oriented districts seem to be exposed to higher vulnerability and to a rapid increase in unemployment in comparison to the rural districts. On the contrary, smaller, peripheral districts respond to a lesser extent or with a delay to the shock. The approach of combining RCI with vulnerability indices provides a new understanding of the resilience-vulnerability relationship. Moreover, a deeper analysis of the Bratislava metropolitan region explains the connection between resilience capacity, economic resilience and vulnerability, as well as between employment and unemployment measures, justifying the need for an integrated approach considering all these concepts together.
Keywords: R11; 330; resilience capacity; vulnerability; Slovak districts (LAU 1)